露蜂房이 t-butylhydroxyperoxide에 의한 Peroxynitrite 생성과 염증성 단백질 발현에 미치는 영향 - 장재식(Jae Shik Jang); 정지천(Ji Cheon Jeong); 신현철(Hyeon Cheol Shin) (동의생리병리학회지, 2007)
Peroxynitrite (ONOO-) is a reactive oxidant formed from superoxide anion radical (·O2-) and nitric oxide (NO), which can oxidize cellular components such as essential protein, non-protein thiols, DNA, low-density lipoproteins and membrane phospholipids. ·O2- and ONOO- have contributed to the pathogenesis of diseases such as stroke, heart disease, Alzheimer's disease and atherosclerosis. Because of damaging effects of ·O2- and ONOO- oxidants, Vespae Nidus, which has been known to strengthen the kidneys to preserve the vital energy. was tested as a potential specific scavenger of those oxidants. In this study, the viability of Vespae Nidus (1, 10, 50 g/ml) to scavenge ·O2-, NO, ONOO- and so to protect cells against tert-butylhydroxyperoxide (t-BHP) induced cell death was tested. The levels of ·O2- and ONOO- were detected by staining with DCFH-DA and DHR 123, respectively. Protein expression levels of COX-2, iNOS and NF-κB were assayed by western blot. Vespae Nidus blocked t-BHP-induced cell death in a dose-dependent fashion. Vespae Nidus inhibited t-BHP-induced production of ·O2-, NO and ONOO- in YPEN cells. The lipid peroxide level was increased and glutathione level was decreased in lipopolysaccharide (LPS)-treated ICR mouse, whereas the ones in the Vespae Nidus-administered group were regulated beneficially. Vespae Nidus inhibited the expression of COX-2, iNOS and NF-κB (p65 and p50) genes in LPS-treated ICR mouse. The present study suggests that Vespae Nidus is a powerful antioxidant and promotes cellular defense activity by scavenging the toxic oxidants such as ·O2- and ONOO-. KCI Citation Count: 3